Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1111/j.1528-1157.1994.tb02908.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Mortality in Status Epilepticus

Abstract: Using univariate and multivariate regression analysis, we studied seizure duration, seizure type, age, etiologies, other clinical features, and mortality among 253 adults with status epilepticus (SE) admitted to the Medical College of Virginia. Cerebral vascular disease and discontinuation of antiepileptic drugs (AEDs) were the most prominent causes of SE, each accounting for approximately 22% of all patients in the series. The other principle etiologies were alcohol withdrawal, idiopathic, anoxia, metabolic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

49
400
8
23

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 613 publications
(483 citation statements)
references
References 20 publications
49
400
8
23
Order By: Relevance
“…Confirming prior studies of SE, we found mortality to be associated with older age (54,55), etiology (54)(55)(56)(57)(58)(59), seizure duration (55,57), and APACHE-2 scores (7).…”
Section: Discussionsupporting
confidence: 70%
“…Confirming prior studies of SE, we found mortality to be associated with older age (54,55), etiology (54)(55)(56)(57)(58)(59), seizure duration (55,57), and APACHE-2 scores (7).…”
Section: Discussionsupporting
confidence: 70%
“…Our data demonstrates that AED weaning did not influence patient discharge disposition, with discharges being evenly distributed between favorable (home, acute rehabilitation), acceptable (SNF, LTACH) and unfavorable (death, hospice) outcomes. Approximately one third of patients died or went to hospice, which is not surprising given that NCS/NCSE in ICU patients is associated with increased mortality and worsened outcome [32], and is in keeping with previous studies that reported mortality rates of about 30% for critically ill patients with seizures lasting greater than one hour [33]. However, the rate of poor outcomes does not appear to be influenced by AED discontinuation.…”
Section: Discussionsupporting
confidence: 68%
“…Prolonged status epilepticus has a higher mortality rate than brief episodes (Towne et al, 1994;DeLorenzo et al, 1995), and is refractory to many currently used medications (Yaffe and Lowenstein, 1993). In clinical testing, lorazepam was more effective than phenytoin in controlling brief overt convulsive status epilepticus (Treiman et al, 1998).…”
Section: Introductionmentioning
confidence: 99%